Genetic Landscape of Amyotrophic Lateral Sclerosis in Czech Patients - Baumgartner, Daniel; Mušová, Zuzana; Zídková, Jana; Hedvičáková, Petra; Vlčková, Eva; Joppeková, Lubica; Kramářová, Tereza; Fajkusová, Lenka; Stránecký, Viktor; Geryk, Jan; Votýpka, Pavel; Mazanec, Radim (Journal of neuromuscular diseases, 2024)
BACKGROUND: Genetic factors are involved in the pathogenesis of familial and sporadic amyotrophic lateral sclerosis (ALS) and constitute a link to its association with frontotemporal dementia (FTD). Gene-targeted therapies for some forms of ALS (C9orf72, SOD1) have recently gained momentum. Genetic architecture in Czech ALS patients has not been comprehensively assessed so far. OBJECTIVE: We aimed to deliver pilot data on the genetic landscape of ALS in our country. METHODS: A cohort of patients with ALS (n = 88), recruited from two Czech Neuromuscular Centers, was assessed for hexanucleotide repeat expansion (HRE) in C9orf72 and also for genetic variations in other 36 ALS-linked genes via next-generation sequencing (NGS). Nine patients (10.1%) had a familial ALS. Further, we analyzed two subgroups of sporadic patients - with concomitant FTD (n = 7) and with young-onset of the disease (n = 22). RESULTS: We detected the pathogenic HRE in C9orf72 in 12 patients (13.5%) and three other pathogenic variants in FUS, TARDBP and TBK1, each in one patient. Additional 7 novel and 9 rare known variants with uncertain causal significance have been detected in 15 patients. Three sporadic patients with FTD (42.9%) were harbouring a pathogenic variant (all HRE in C9orf72). Surprisingly, none of the young-onset sporadic patients harboured a pathogenic variant and we detected no pathogenic SOD1 variant in our cohort. CONCLUSION: Our findings resemble those from other European populations, with the highest prevalence of HRE in the C9orf72 gene. Further, our findings suggest a possibility of a missing genetic variability among young-onset patients.
Keywords: DNA vazebné proteiny; dospělí; protein C9orf72; DNA Repeat Expansion; Amyotrophic lateral sclerosis; frontotemporální demence; expanze repetic DNA; Female; věk při počátku nemoci; protein FUS vázající RNA; Adult; RNA-Binding Protein FUS; ženské pohlaví; gene variants; High-Throughput Nucleotide Sequencing; lidé; next-generation sequencing; Protein Serine-Threonine Kinases; neurogenetics; genetická predispozice k nemoci; Genetic Predisposition to Disease; amyotrofická laterální skleróza; kohortové studie; Middle Aged; Cohort Studies; Male; Aged; Czech Republic; Frontotemporal Dementia; vysoce účinné nukleotidové sekvenování; Amyotrophic Lateral Sclerosis; DNA-Binding Proteins; Česká republika; lidé středního věku; Age of Onset; C9orf72 Protein; senioři; mužské pohlaví; mutation screening; C9orf72 repeat expansion; protein-serin-threoninkinasy; Humans